IMPLEMENTASI KEBIJAKAN PENATAAN DAN STRATEGI INOVASI PENERTIBAN PEDAGANG KAKI LIMA KOTA JAYAPURA - Sawir, Muhammad; Idris, Muhammad Farid (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2024)
The Jayapura City Government has carried out various activities to regulate and control street vendors in the city. These efforts have had an impact on reducing conflict between the Civil Service Police Unit and street vendors. This shows that the city government has to some extent met the expectations of street vendors. The aim of this research is to analyze the implementation of policies regarding street vendors in Jayapura City. The research was conducted in Jayapura City, with street vendor informants. Data is collected through observations, interviews and document studies, and analyzed and finally draws conclusions. Research findings show that the implementation of structuring and controlling street vendors in Jayapura City began with regional regulation number 14 of 2001. In addition, street vendors believe that policy implementation focuses more on structuring rather than controlling. The city government has succeeded in creating a clean, orderly, beautiful, comfortable and safe environment for street vendors' businesses. They have also established integrated arrangements for street vendors that are in line with sustainable spatial planning, while increasing community participation in organizing and coaching them. However, it was found that this policy was still unable to improve welfare through developing informal sector trading activities for street vendors.